2021
DOI: 10.3390/s21175977
|View full text |Cite
|
Sign up to set email alerts
|

Small-Angle Particle Counting Coupled Photometry for Real-Time Detection of Respirable Particle Size Segmentation Mass Concentration

Abstract: Respirable particulate matter air pollution is positively associated with SARS-CoV-2 mortality. Real-time and accurate monitoring of particle concentration changes is the first step to prevent and control air pollution from inhalable particles. In this research, a new light scattering instrument has been developed to detect the mass concentration of inhalable particles. This instrument couples the forward small-angle single particle counting method with the lateral group particle photometry method in a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Real-time, rapid and high-resolution monitoring of particulate matter concentration changes is the first step to prevent and control inhalable particulate matter pollution. For the measurement of aerosol particle mass concentration by light scattering method, Rongrui Zhang designed a portable device for measuring the mass concentration of particulate matter at a forward angle, and proved that the scattered light intensity can effectively invert the mass concentration of particulate matter [5]. Based on Mie scattering theory, it is found that the mass sensitivity of the light scattering mass concentration instrument is affected by the physical characteristics of particles, such as particle size, refractive index, sphericity and density [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Real-time, rapid and high-resolution monitoring of particulate matter concentration changes is the first step to prevent and control inhalable particulate matter pollution. For the measurement of aerosol particle mass concentration by light scattering method, Rongrui Zhang designed a portable device for measuring the mass concentration of particulate matter at a forward angle, and proved that the scattered light intensity can effectively invert the mass concentration of particulate matter [5]. Based on Mie scattering theory, it is found that the mass sensitivity of the light scattering mass concentration instrument is affected by the physical characteristics of particles, such as particle size, refractive index, sphericity and density [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Before measuring, more complex calibration experiments are required to determine the parameters of the instrument [30][31][32][33]. When the measurement environment differs greatly from the calibration environment, the measurement results tend to have large errors [34]. This is also the most problematic problem in measuring the mass concentration of PM using light scattering.…”
Section: Introductionmentioning
confidence: 99%
“…The ICPMS is a highly sensitive and rapid analytical technique for elemental analysis at ultra-low concentrations. The samples in traditional ICPMS are usually metal ions dissolved in solution, and the concentration of total metal can be calculated based on the averaged intensity of the ion peak over a measuring period 6 .…”
Section: Introductionmentioning
confidence: 99%